Chain-End Modifications and Sequence Arrangements of Antimicrobial Peptoids for Mediating Activity and Nano-Assembly - Hasan, Abshar; Saxena, Varun; Castelletto, Valeria; Zimbitas, Georgina; Seitsonen, Jani; Ruokolainen, Janne; Pandey, Lalit M.; Sefcik, Jan; Hamley, Ian W.; Lau, King Hang Aaron (Frontiers in Chemistry, 2020)
Poly(N-substituted glycine) “peptoids” are an interesting class of peptidomimics that can resist proteolysis and mimic naturally found antimicrobial peptides (AMPs), which exhibit wide spectrum activity against bacteria. This work investigates the possibility of modifying peptoid AMP mimics (AMPMs) with aliphatic lipid “tails” to generate “lipopeptoids” that can assemble into micellar nanostructures, and evaluates their antimicrobial activities. Two families of AMPMs with different distributions of hydrophobic and cationic residues were employed—one with a uniform repeating amphiphilicity, the other with a surfactant-like head-to-tail amphiphilicity. To further evaluate the interplay between self-assembly and activity, the lipopeptoids were variously modified at the AMPM chain ends with a diethylene glycol (EG2) and/or a cationic group (Nlys-Nlys dipeptoid) to adjust amphiphilicity and chain flexibility. Self-assembly was investigated by critical aggregation concentration (CAC) fluorescence assays and dynamic light scattering (DLS). The structure of a key species was also verified by small-angle X-ray scattering (SAXS) and cryo-electron microscopy (cryo-EM). To screen for antibacterial properties, we measured the minimum inhibitory concentrations (MIC) against S. aureus, E. coli and P. aeruginosa. We found that certain combinations of lipid tail and AMPM sequences exhibit increased antibacterial activity (i.e. decreased MICs). Perhaps counter-intuitively, we were particularly interested in increased MICs in combination with low CACs. Concealing antimicrobial interactions due to packing of AMPMs in nano-assemblies could pave the way to AMPMs that may be “inert” even if unintentionally released and prevent microbes from gaining resistance to the lipopeptoids. Overall, incorporation of EG2 significantly improved lipopeptoids packing while the hydrophobic tail length was found to have a major influence over the MIC. One particular sequence, which we named C15-EG2-(kss)4, exhibited a very low CAC of 34 M (0.0075 wt.%) and a significantly increased MIC above values for the unmodified AMPM. With the sequence design trends uncovered from this study, future work will focus on discovering more species such as C15-EG2-(kss)4 and on investigating release mechanisms and the potency of the released lipopeptoids.